The effect of ankle strengthening exercise on balance in youth basketball players - Pratama D. Nugraha; Soegiyanto Soegiyanto; Agus Kristiyanto; Mahalul Azam (IP Iermakov S.S., 2022)
Background and Study Aim. Balance is an important factor in basketball. Thus, the low level of balance needs to be improved to support future achievements of youth basketball players. The aim of study is to determine the influence of bosu ball exercises and theraband exercise on the balance of basketball players aged 16 and 18 years old. Material and Methods. The research design used is experimental research with 2x2 factorial analysis. The level of significance was set a 0.05 for all samples. In the study participated 64 men's basketball players aged 16 years old (n=32) and 18 years old (n=32). Players were each divided into 4 sample groups of 8 players. Results. The test results before the experiment and after the experiment showed that in all groups there were various changes in the balance. There is a more significant change in balance after performing exercises with the ball bosu in the group of 16 years old. In the 18-year-old group, there is a more significant change in balance after performing theraband exercises. Conclusions. Characteristics of the age group of 16 years and 18 years are not much different. Bosu ball exercises give a better effect than theraband exercise.